Teknik Penerjemahan Pronomina Persona Pertama dalam Gim Dreadout 2 dari Bahasa Inggris ke dalam Bahasa Indonesia - Haura Nabila Rinaldi; Doni Jaya (Universitas Sebelas Maret, 2024)
Game subtitle must be translated using proper techniques to avoid misunderstanding when the game is played. In addition, Indonesian and English have different systems of personal pronouns, which must be known and understood by the translator. Indonesian has several parameters of personal pronouns heavily influenced by various aspects of interpersonal relationship between speakers. This research used the descriptive qualitative method. Data in the form of sentences containing personal pronouns were taken from Dreadout 2’s English subtitle and its Indonesian translation. This research used two sets of theory: Molina and Albir’s translation technique (2002) and Moeliono, et al.’s parameters of Indonesian personal pronouns (2017). Results show that the translator used three techniques, i.e. established equivalence, particularization, and variation, to translate the English pronouns. Besides that, the selection of Indonesian personal pronouns as equivalents was found to be deeply influenced by the parameters of social status and kinship.